2022
DOI: 10.1530/jme-22-0067
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular basis for the action of retinoic acid in spermatogenesis

Abstract: Spermatogenesis is a highly organized and regulated process that requires the constant production of millions of gametes over the reproductive lifetime of the mammalian male. This is possible because of an active stem cell pool and an ordered entry into the germ cell developmental sequence. The ordered entry is a result of the synthesis and action of retinoic acid allowing for the onset of spermatogonial differentiation and an irreversible commitment to spermatogenesis. The periodic appearance and actions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Several Sertoli cell expressed proteins, such as the type III intermediate filament proteins vimentin, desmin and peripherin (Mruk and Cheng, 2004, Vogl et al, 2008) as well as fatty acid-binding protein 5 (FABP5) and intracellular retinol-binding protein 1 (RBP1) (Oresti et al, 2013, Griswold, 2022), were found to be higher abundant in Actl7b-/- testicular samples. Differential abundance of these mostly Sertoli cell enriched proteins might indicate a secondary effect caused by arrested and apoptotic germ cells.…”
Section: Resultsmentioning
confidence: 99%
“…Several Sertoli cell expressed proteins, such as the type III intermediate filament proteins vimentin, desmin and peripherin (Mruk and Cheng, 2004, Vogl et al, 2008) as well as fatty acid-binding protein 5 (FABP5) and intracellular retinol-binding protein 1 (RBP1) (Oresti et al, 2013, Griswold, 2022), were found to be higher abundant in Actl7b-/- testicular samples. Differential abundance of these mostly Sertoli cell enriched proteins might indicate a secondary effect caused by arrested and apoptotic germ cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, at stage IX–XII, there were no significant differences between WT and Rhox8 KO, indicating a normal spermatogenesis during this period, which implies a crucial role of Rhox8 at the stage VII–VIII rather than at the later stages including spermiation. Taking into account that the action of retinoic acid is required for spermatogonial differentiation and that the level of retinoic acid is high at stage VII–VIII when type A spermatogonia differentiate into type A1 spermatogonia [48, 49], the highest level of Rhox8 expression at stage VII and VIII implies a possible role of Rhox8 in retinoic acid signaling pathway during spermatogonia differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ATRA is known to modulate uterine receptivity and facilitate embryo implantation by promoting the secretion of uterine factors necessary for embryo attachment and placental development [141,142]. Additionally, ATRA plays a pivotal role in male reproduction, influencing processes such as spermatogenesis, testicular development, and sperm production and motility [143,144].…”
Section: Growth Cellular Differentiation Morphogenesis and Reproducti...mentioning
confidence: 99%